SISTEM PENILAIAN KINERJA DOSEN PNS.Dpk DI LINGKUNGAN KOPERTIS WIL II MENGGUNAKAN METODE ANALYTICAL HIERACHY PROCESS (AHP) - Dona Yuliawati; Wasilah Wasilah (Jurnal Informatika, 2012)
The PNS Dpk lecturer is part for private universities as a lecturer chief next by KOPERTIS. It is expected to be an example for other lecturers / role in each, PTS either in the TRIDARMA college and performance indicators other kopertis with the rules. Judgment lecturer PNS DPK can be conducted easily and automated, that is by using models system supporting decision corresponding to criteria as stipulated by KOPERTIS, especially KOPERTIS region II. Model that can be referred to that can be used is a model Analytical Hierarchy Process (AHP). The application of this model is done through phases: data collection, determination of the main criteria and and sub criteria in the assessment criteria and weighting lecturer, sub criteria, the determination of the priority and implementation using Software Expert choice.Based on application of the method of Analytical Hierarchy Process (AHP), it can be noted that the criteria have been defined, namely educational teaching, research, outreach and supporting elements.Key word : Performance, AHP (Analytical Hierarchy Process) and Expert choice.